2021
DOI: 10.1140/epjc/s10052-021-08884-5
|View full text |Cite
|
Sign up to set email alerts
|

Critical exponents of the O(N)-symmetric $$\phi ^4$$ model from the $$\varepsilon ^7$$ hypergeometric-Meijer resummation

Abstract: We extract the $$\varepsilon $$ ε -expansion from the recently obtained seven-loop g-expansion for the renormalization group functions of the O(N)-symmetric model. The different series obtained for the critical exponents $$\nu ,\ \omega $$ ν , ω and $$\eta $$ η have been resummed using our recently introduced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 59 publications
(263 reference statements)
2
73
3
Order By: Relevance
“…Our aim in the present paper is to demonstrate that the accuracy of self-similar factor approximants for the O(N) -symmetric ϕ 4 theory in three dimensions can be drastically improved by employing the available seven-loop ε-expansions that are known for N = 1 [25] and are derived, using the seven-loop coupling parameter expansions [26], in Ref. [27] for N = 0, 1, 2, 3, 4. These expansions are as follows.…”
Section: Critical Exponentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our aim in the present paper is to demonstrate that the accuracy of self-similar factor approximants for the O(N) -symmetric ϕ 4 theory in three dimensions can be drastically improved by employing the available seven-loop ε-expansions that are known for N = 1 [25] and are derived, using the seven-loop coupling parameter expansions [26], in Ref. [27] for N = 0, 1, 2, 3, 4. These expansions are as follows.…”
Section: Critical Exponentsmentioning
confidence: 99%
“…The results of this calculation for the exponent ν are illustrated in Table 1. Following the same procedure for the exponents η and ω, we obtain the values shown in Table 2, where we compare the results obtained by means of factor approximants (FA) with those of other methods: Monte Carlo simulations (MC) [28][29][30][31][32][33], Conformal bootstrap (CB) [34][35][36][37][38], Hypergeometric Meijer summation (HGM) [27], Borel summation complimented by additional conjectures on the behavior of coefficients (BAC) [39], Borel summation with conformal mapping (BCM) [40], and Nonperturbative renormalization group (NPRG) [5,[41][42][43].…”
Section: Critical Exponentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution equation for u should be obtained by substituting (36) into (28). However, in general case the equation will be incompatible with the LPA ansatz so the task is to satisfy it approximately.…”
Section: Lpamentioning
confidence: 99%
“…To this end in the present paper a multi-step renormalization technique will be suggested that makes possible the use of different renormalization methods at different stages of the RG flow. For example, this will allow one to use LPA within the transient region at an early stage of renormalization when the interactions are strong [1] and to switch to the perturbative treatment in the critical region where, for example, the DE expansion can be efficient [22,27,28].…”
Section: Introductionmentioning
confidence: 99%